Violência nas escolas públicas de cascavel/pr e a judicialização: constatações e apontamentos - Araujo Filho, Ismael Kalil Saffe de (2017)
As an object of great concern and attention from the state and the whole society, violence in school has been taking significant proportions, especially in the public school system. Given this situation, the judicialization has been constituted as a recurrent way to face some forms of school violence. However, it is questionable: What are the practical effects and effectiveness (or not) of the school violence judicialization? What are the impressions of some members of the Tutelary Council and of the school about the problems of school violence in the Judiciary? Through a qualitative and descriptive research in the city of Cascavel-PR, we interviewed responsible counselors from each Tutelary Council and directors of twenty public schools in Cascavel-PR, in which ten directors are from municipal schools and ten from state schools. Based on the collected data, it was verified how is the interaction between school and Tutelary Council, highlighting the action of these two institutions in cases of violence, identifying what are the providences taken both by the school and by the Tutelary Council and also what are the effects of these providences in relation to the effective resolution of the problem, especially in relation to the judicialization. The survey revealed some perceptions on the part of the members of the school regarding the need to qualify the interaction with the Tutelary Council. The members of the tutelary council, in turn, consider that there is a lack of preparation to deal with the phenomenon of school violence in the schools' pedagogical team. It was also observed that the judicialization, besides being time-consuming, is not effective in solving or alleviating the problem of school violence, and that the Restorative Justice, even if little diffused, is the most appropriate providence when there is an act of school violence, in infractions cases.